Institutional Capacity Development for Public Street Lighting Services at the West Java Provincial Transportation Agency - Deni Yusfadila; Ismail Nurdin; Dyah Poespita Ernawati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Rapid population growth in West Java Province has directly contributed to increased mobility and higher traffic volumes on public roads. To support road safety, security, and the smooth flow of traffic at night, the provision of adequate public street lighting has become a critical public service requirement. However, in practice, the management of public street lighting along provincial roads continues to face several challenges, including the uneven distribution of street lighting installations, recurring failures of electrical components, and slow emergency response times due to the extensive geographical coverage and the absence of a real-time monitoring system. This study aims to analyze the institutional capacity development of public street lighting services at the West Java Provincial Department of Transportation, with a particular focus on the Regional Technical Implementation Unit (UPTD) for the Management of Land Transportation Infrastructure and Traffic (LLAJ) Region III. These institutional challenges are attributed to shortages of qualified technical personnel, inadequate operational facilities and infrastructure, suboptimal monitoring mechanisms, and limited budget allocations. The findings indicate that the current management of public street lighting has not yet achieved optimal performance. This is reflected in the low level of street lighting coverage along provincial roads within the operational area of the UPTD for the Management of Land Transportation Infrastructure and Traffic (LLAJ) Region III, which has reached only 31.16% of the total required coverage. Institutional constraints are further evidenced by vacant functional positions for traffic facilities personnel, a limited number of skylift vehicles, inconsistent maintenance budgets, and a weak integrated control system. The primary barriers to institutional capacity development include budget limitations, shortages of competent human resources, the extensive geographical area, and insufficient operational support facilities. Efforts to enhance institutional capacity include strengthening interagency coordination, improving the quality of human resources, optimizing planning processes, and developing adaptive technical strategies through the implementation of a simple, responsive, and digitally based public complaint reporting system. This study is expected to contribute theoretically to the literature on public sector organizational capacity development while providing practical recommendations for the West Java Provincial Department of Transportation to improve the quality of public street lighting services.